Teenage girls sitting and writing on the steps of a building - Unknown:::Creator::::::::::::
Photograph shows three teenage girls sitting on the steps of a building. One of them is writing on paper she holds in her lap. One of the other girls is writing on paper that the third girl is holding in her lap. They are probably campers at the YWCA's Camp Ayun Mapu in Big Basin, California.